2019
DOI: 10.1002/chem.201900988
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Binders Constructed through Dynamic Noncovalent Bonds for High‐Capacity Silicon‐Based Anodes

Abstract: Silicon (Si) is a promising candidate for high‐capacity anode materials owing to its high theoretical capacity (3579 mAh g−1), low working voltage, and wide natural abundance, although its huge volume variation during charge/discharge processes always results in a short cycling life. Polymer binders play a vital role in improving the cycling performance of Si‐based anodes, although traditional polyvinylidene difluoride cannot fulfil the requirements owing to its weak van der Waals forces with the Si surface. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 97 publications
(111 reference statements)
0
36
0
Order By: Relevance
“…Most of reviews on binders are mainly reported from the perspective of the type, [33] properties, [34] structure, [35] and dynamic bonds. [36] In addition, although there are some studies concerning the influence of interfacial bonding force, molecular structure and other factors on the performance of binders, there is still a lack of systematic and comprehensive discussions on the key factors affecting the performance of binders.…”
Section: Introductionmentioning
confidence: 99%
“…Most of reviews on binders are mainly reported from the perspective of the type, [33] properties, [34] structure, [35] and dynamic bonds. [36] In addition, although there are some studies concerning the influence of interfacial bonding force, molecular structure and other factors on the performance of binders, there is still a lack of systematic and comprehensive discussions on the key factors affecting the performance of binders.…”
Section: Introductionmentioning
confidence: 99%
“…32 Self-healing polymers based on ionic interactions can find applications in many fields such as the development of artificial e-skin devices, 32 microfluidic, therapeutic, 31 anti-fouling coatings, 33 and high-capacity Si-electrodes. 34 Among telechelic oligomers with ionic (acid-base) interactions, 23,24 Indeed, in the case of hydroxyl-terminated PDMS, they showed an increase in the T g value due to a decrease in the chain length. 24 This behavior, in contrast with results obtained with hydroxyl-terminated poly(propylene glycol), (PPG), was observed also in the case of amino-terminated and carboxylic-terminated telechelic PDMS, 23 and other low Tg polymers with polar end groups.…”
Section: Introductionmentioning
confidence: 99%
“…In case just ionic interactions are present in the network, either two oppositely charged ions or ions and induced‐dipole functions are involved, such as in telechelic oligomers terminated with acid and amine groups, 27,28 self‐healing poly(ethylene‐co‐methacrylic acid) based‐ionomers, 29,30 zwitterionic polymers, 31 polyelectrolyte complexes, and polymers with metal ion interactions 32 . Self‐healing polymers based on ionic interactions can find applications in many fields such as the development of artificial e‐skin devices, 32 microfluidic, therapeutic, 31 anti‐fouling coatings, 33 and high‐capacity Si‐electrodes 34 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such binders are not applicable for electrode manufacturing. [31] Recently, physically crosslinked polymers [32][33][34][35] have been reported as binders, exhibiting selfhealing and being deformable. These high-strain polymers are not only capable of effectively accommodating and enduring the volume change, but releasing local stress through chains slip and physically sacrificial interactions facture, thus reducing the destruction of electrodes.…”
mentioning
confidence: 99%